Writing to template: Researchers' negotiation of procedural research ethics. (June 2020) - Chiumento, Anna; Rahman, Atif; Frith, Lucy
Abstract: This qualitative study examines researchers' views of research ethics in everyday global mental health research practice. We present data from a multi-site study conducted in 2014-15 involving 35 individual in-depth interviews that explore researchers' perceptions of procedural ethics in research conducted in South Asia. We examine how researchers' negotiate ethical procedures, and consider the impact this has on ethical practice. This study foregrounds researchers' pivotal role in procedural research ethics: they produce ethical documents including research protocols and informed consent forms; engage in ethical review; and apply ethical documents to research practice. We apply the analytical framework of boundary objects to show the active work that ethical documents simultaneously enable and inhibit as researchers and ethical review boards apply these as templates for interaction. This analysis shows how the documents required by procedural ethics processes facilitate representations of research that are generalised, standardised, and abstracted from the situated context in which they are applied. Researchers' engagement with these standardised forms cannot prepare them for potential ethical issues in research practice. These templates therefore act as ideal constructions of what research ethics could be, documenting moral intent that researchers draw upon to translate into practice. Highlights: Qualitative study of researchers' negotiation of procedural ethics material objects. Developed by researchers and ERBs, these material objects act as boundary objects. Researchers position these objects differently when acting towards each social world. These objects both promote and constrain researcher preparation for ethical practice.